Analysis of the Potential Development of Sa'o Traditional House Tourism in Bajawa Ethnic Communities, Ngada District - Fransiskus Xaverius Rema; Enok Maryani (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2022)
Tourism is an industrial sector that provides many benefits for survival, one of which is economic benefits. Tourism consists of three parts: style, culture, and artificial. One of the tours that are currently being developed is cultural tourism. Cultural tourism is tourism that displays local wisdom to attract tourists. One cultural tour that requires management development is the cultural tourism of the Sa'o traditional house in Ngada Regency, East Nusa Tenggara Province. The Sa'o traditional house is an original traditional house belonging to the Bajawa ethnic community, which is in the traditional Bena village. This study aims to analyze the cultural tourism potential of the Sa'o traditional house for tourism development. The research method used in this research is mini research which is qualitative with a literature study approach. This research is a type of library research. The study results show that the Sa'o traditional house located in the traditional village of Bena has enormous potential to be developed and promoted in cultural tourism. The Sa'o traditional house has its characteristics: special sections consisting of teda Wewa, teda one, and one. The Sa'o traditional house has a symbolic meaning for the Bajawa ethnic community consisting of Ngadhu, Bhaga, Watu Lewa, and Nabe. In developing the cultural tourism of the Sa'o traditional house, the participation of the government and the surrounding community is needed. An analysis of the inhibiting factors for cultural tourism of the Sa'o traditional house is needed.Keywords: Sa'O Traditional House, Bajawa Ethnicity, Cultural Tourism, Development